2021
DOI: 10.3916/c67-2021-06
|View full text |Cite
|
Sign up to set email alerts
|

Internet memes in Covid-19 lockdown times in Poland

Abstract: Poland was one of the countries that was hit by the Covid-19 pandemic in 2020, and its government imposed restrictions to combat the spreading of the virus. The Internet and social media became outlets for people’s reactions to the events that unfolded, including the lockdown. A part of this reaction came in the form of creating and sharing memes – an expression of digital participatory culture. This paper aims to analyze how Covid-19 was communicated and narrated through Internet memes and how they presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
3
10
0
4
Order By: Relevance
“…Interestingly, we observed that while English memes often used celebrities (e.g., movie and TV actors and singers) to refer to ordinary people, Chinese memes largely employed popular Internet characters (such as 'Panda Man' or person with a panda-like head, and 'a girl with mushroom-shaped head') to refer to a particular actor. This result is consistent with (Norstrom and Sarna, 2021)'s study focusing on COVID-19 meme use in Poland, which showed that 'ordinary men' is the most prominent actor. While the unique categories identified in the English memes are 'politician,' (9%), 'media figures,' (3%), and 'animal' (3%), those found in the Chinese memes are 'authority,' (4.9%), and 'humanized virus,' (9.8%).…”
Section: Actors Involved In the Issuessupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, we observed that while English memes often used celebrities (e.g., movie and TV actors and singers) to refer to ordinary people, Chinese memes largely employed popular Internet characters (such as 'Panda Man' or person with a panda-like head, and 'a girl with mushroom-shaped head') to refer to a particular actor. This result is consistent with (Norstrom and Sarna, 2021)'s study focusing on COVID-19 meme use in Poland, which showed that 'ordinary men' is the most prominent actor. While the unique categories identified in the English memes are 'politician,' (9%), 'media figures,' (3%), and 'animal' (3%), those found in the Chinese memes are 'authority,' (4.9%), and 'humanized virus,' (9.8%).…”
Section: Actors Involved In the Issuessupporting
confidence: 91%
“…'Regulation' (i.e., rules/preventive measures issued by government institutions) accounts for the largest overall percentage of the identified issues in Chinese and English data groups (56% and 37% respectively, example 1 (Appendix: Figure 1) and 2 (Appendix: Figure 2)). This result aligns with (Norstrom and Sarna, 2021)'s study focusing on COVID-19 memes in Poland, showing that 'bans and orders' is the most prominent issue. This result can be explained by the framing theory: people across cultures tend to use internet memes to emphasize the most pressing challenges brought about by the pandemic (e.g., sheltering-in-place, social distancing).…”
Section: Issues Addressed By Covid-19 Memessupporting
confidence: 88%
“…The benefits of sharing humorous political memes include making political commentary accessible and strengthening solidarity (Penney, 2020). A study of pandemic memes shared in Poland revealed commentary about restrictions and expressed dissatisfaction with the government and police (Norstrom & Sarna, 2021). Similarly, some pandemic memes provided a political critique by mocking those who wore masks incorrectly (Dynel, 2021).…”
Section: Internet Culture During the Pandemicmentioning
confidence: 99%
“…Need hõlmavad mälestusi sotsialismiajast -näiteks filmidest ja meeldejäävatest karakternäitlejatest -, mis osutavad paralleelidele mineviku ja tänapäeva vahel ning kommenteerivad humoorikal moel COVIDpandeemia aegset absurdset reaalsust. Seda valikut toetab hiljutine uurimus, mis sedastas, et kuni 30% poola meemidest sisaldab viiteid kohalikule kultuurile, eelkõige filmikunstile (vt Norström & Sarna 2021).…”
Section: Meetodunclassified